Evaluación de impacto ambiental con enfoque de ciclo de vida de las unidades menores de hidrocarburos del Departamento de Loreto - Chavez Marin, Nancy Magaly (2024)
Economic activities must maintain a balance in their processes or services to verify the system's inflow and outflow. Therefore, we propose evaluating the environmental impacts of minor hydrocarbon units in the Loreto department, adopting a comprehensive life cycle approach. The methodology employed was an analytical observational approach, retrospective in nature and cross-sectional in design, considering all minor hydrocarbon units in the Loreto department as the study population. The results show that 69% of these units are land-based establishments, with most of the storage being 84-octane gasoline. The most vulnerable components are the flora and fauna, while the activity primarily impacts air quality, justifying the estimation of air quality and noise on a quarterly basis. Additionally, the temporary and partial abandonment of these units is a priority. It is concluded that the maximum water consumption is 30 m³ and energy consumption is 1325 kWh. The generation of non-hazardous waste is 0.0018 tons and hazardous waste is 0.0013 tons